อนาคตภาพองค์การพยาบาล โรงพยาบาลมหาวิทยาลัยของรัฐ ในช่วงพุทธศักราช 2555-2559 - จันทรา แก้วภักดี (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To explore scenario of nursing organization, government university hospitals during B.E. 2012-2016. The Ethnographic Delphi Futures Research technique was applied. The subjects were 18 experts in nursing organization including chief administrator from Ministry of Public Health, nursing administrators, nursing organizations, and administrative lecturers from government university hospitals. Research methodology was conducted as 3 steps. Step1, the experts were described about the scenario of nursing organization, government university hospitals during B.E. 2012-2016. Step 2, data were analyzed by using content analysis for developing the rating scales questionnaire. All items in the questionnaire were ranked the level probability of scenario by a prior panel of expert. Step 3, data were analyzed by using median and interquatile range was develops a new version of the questionnaire. Data were analyzed again by median and interquatile range to summarize the scenario of nursing organization. The results of this study were presented that the scenario of nursing organization, government university hospitals during B.E. 2012-2016 consist of 5 aspects as follow : 1) scenario of nursing services to upgrade standard of nursing services, quality of nursing services, and develop the way of health services, 2) scenario of nursing administration using good governance, and develop the way of communication, 3) scenario of human resource development, capacity and pushing an excellent personnel forward, 4) scenario of academic and research, management to follow knowledge of nursing and nursing research, and 5) scenario of supporting studied administration, to raise a standard of academic and develop potentiality of a wise man and control standard of academic.